THE USE OF READING LOGS METHOD TO IMPROVE STUDENTS’ READING SKILL TO THE EIGHTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL FITRA ABDI PALEMBANG - Whissa Gusti Shandiya; Djunaidi; Yus Vernandes Uzer (Esteem Journal of English Education Study Programme, 2024)
Reading logs are a method that can be used to make it easier for students to understand text or a reading in English subjects that aims to make a small note to remember important things in reading. With this method, researcher aim to improve students' skill in reading well. This research has several stages, which include the observation stage, preparation stage, implementation stage, and final stage. At that stage, the researcher conducted a pre-test and post-test to get the initial value and changes in students' reading skill using the reading logs method in the final stage. From the results of the research, researcher found significant changes in the reading skill of students with the following detailed results: skills worth 0.081 in the experimental class and 0.067 in the control class, exceeding the significant value ≥ α = 0.05. and a statistically significant value of 0.374 was declared homogeneous because it was greater than the significant level of 0.05 and in accordance with the hypothesis test that has been tested has a significant value of 0.000 and a significant level of 0.05, it has a significant effect in the application of the reading logs method.